Environmental Controls of Diffusive and Ebullitive Methane Emissions at a Subdaily Time Scale in the Littoral Zone of a Midlatitude Shallow Lake. Issue 9 (18th September 2020) - Taoka, T.; Iwata, H.; Hirata, R.; Takahashi, Y.; Miyabara, Y.; Itoh, M.
Abstract: Environmental controls on methane (CH4 ) emission from lakes are poorly understood at subdaily time scales due to a lack of continuous data, especially for ebullition. We used a novel technique to partition eddy covariance CH4 flux observed in the littoral zone of a midlatitude shallow lake in Japan and examined the environmental controls on diffusion and ebullitive CH4 flux separately at a subdaily time scale in different seasons. Using the high‐frequency data, we investigated how CH4 accumulation in the water and sediment layers alters the dynamics and environmental controls of fluxes. The contribution of ebullitive flux to total flux was 57% on average. Environmental controls of diffusive and ebullitive fluxes known in the literature were confirmed. We further found that the environmental controls were different in different seasons and suggested that additional consideration of CH4 accumulation could explain the variability. The transfer of accumulated dissolved CH4 from the bottom water layer to the surface in summer and the accumulation of dissolved CH4 under surface ice in winter were suggested to be important for explaining the variability of diffusive flux. In summer, a higher ebullitive flux tended to occur following triggers such as a decrease in hydrostatic pressure. In winter, the impact of triggers was not obvious, and a higher ebullitive flux tended to occur in the morning. We suggested that the low CH4 production rate in winter slowed the replenishment of bubbles in the sediment, negating the effect of triggers on ebullition. Plain Language Summary: Lakes are one of the main natural sources of methane (CH4 ). Methane is emitted from lake sediments to the atmosphere via diffusion through the water column and episodic emission of bubbles (ebullition). Currently, environmental controls at subdaily time scales are poorly understood due to a lack of continuous data, especially for ebullition. We applied a new technique to partition continuous CH4 flux data obtained with the eddy covariance technique in a midlatitude shallow lake into diffusive and ebullitive fluxes and examined their environmental controls separately. We confirmed that the diffusive flux increased with increasing wind speed and increasing dissolved CH4 concentrations in the surface water as known in the literature. We further suggested that for this shallow lake, the transfer of accumulated dissolved CH4 from the bottom water layer to the surface under thermally stratified conditions was important for explaining the variability in diffusive flux. In summer, a higher ebullitive flux tended to occur following a decrease in hydrostatic pressure. In winter, however, the impact of triggers was not obvious. We suggested that, in winter, the low CH4 production rate slowed the replenishment of bubbles in the sediment, negating the effect of triggers on ebullition. Key Points: Partitioned diffusive and ebullitive methane fluxes from a shallow lake were examined for their subdaily environmental controls The subdaily environmental controls of diffusive and ebullitive fluxes were different in different seasons The accumulations of methane in the water and sediment were suggested to alter the environmental controls of fluxes between seasons